Case Report: A Rare Case Cellular Angiofibroma Presenting as an Inguinal Mass in Male Patient - AlSairafi, Rani A. (Journal of Posthumanism, 2025)
Cellular angiofibroma is a rare, benign mesenchymal tumor, typically arising in the inguinoscrotal region of males and the vulvovaginal region in females. [1,2] This case report presents a 51-year-old male with a left inguinal mass, ultimately diagnosed as a cellular angiofibroma following imaging, surgical excision, and histopathological evaluation.